Keefektifan Pembelajaran Berdiferensiasi Menggunakan “Kaktarsi” dalam Pembelajaran Bahasa Indonesia - Alamsari, Alamsari (Jurnal Didaktika Pendidikan Dasar, 2024)
The research aims to describe the effectiveness of implementing differentiated learning using the Creative Word Cards (Kaktarsi) media to increase the activeness of learning Indonesian in class IX students at SMPN 1 Indralaya Utara. This research aims to describe how differentiated learning is implemented using KaK TarSi media to increase the activeness of learning Indonesian in class IX students at SMPN 1 Indralaya Utara. This type of research is pre-experimental research with a population sample of 30 students. The research design used was one group pretest-posttest design. From the research results, it is known that there is an increase in student activity in learning activities, namely students listen to the teacher’s explanation (13%), submit assignments on time (24%), actively discuss with colleagues (30%), and ask questions to the teacher or colleagues ( 33%). From the results of the gain, it is known that there is an increase in activity before and after learning by 25%. Thus, it can be concluded that differentiated learning using KaK TarSi media can increase student learning activity.